Free-standing bilayered vanadium oxide films synthesized by liquid exfoliation of chemically preintercalated δ-LixV2O5·nH2O. Issue 8 (24th March 2021) - Houseman, Luke; Mukherjee, Santanu; Andris, Ryan; Zachman, Michael J.; Pomerantseva, Ekaterina
Abstract : A free-standing film composed of bilayered vanadium oxide nanoflakes is for the first time synthesized using a new low-energy process. Abstract : A free-standing film composed of bilayered vanadium oxide nanoflakes is for the first time synthesized using a new low-energy process. The precursor powder, δ-Li x V2 O5 · n H2 O, was prepared using a simple sol–gel based chemical preintercalation synthesis procedure. δ-Li x V2 O5 · n H2 O was dispersed and probe sonicated in N -methyl pyrrolidone to exfoliate the bilayers followed by vacuum filtration resulting in the formation of a free-standing film with obsidian color. X-ray diffraction showed lamellar ordering of a single-phase material with a decreased interlayer distance compared to that of the precursor powder. Scanning electron microscopy images demonstrated stacking of the individual nanoflakes. This morphology was further confirmed with scanning transmission electron microscopy that showed highly malleable nanoflakes consisting of ∼10–100 vanadium oxide bilayers. One of the most important consequences of this morphological rearrangement is that the electronic conductivity of the free-standing film, measured by the four-probe method, increased by an order of magnitude compared to conductivity of the pressed pellet made of precursor powder. X-ray photoelectron spectroscopy measurements showed the coexistence of both V 5+ and V 4+ oxidation states in the exfoliated sample, possibly contributing to the change in electronic conductivity. The developed approach provides the ability to maintain the phase purity and crystallographic order during the exfoliation process, coupled with the formation of a free-standing film of enhanced conductivity. The produced bilayered vanadium oxide nanoflakes can be used as the building blocks for the synthesis of versatile two-dimensional heterostructures to create innovative electrodes for electrochemical energy storage applications.